Temporal trends and global burden of urolithiasis: a comparative analysis of incidence, prevalence, mortality, and disability-adjusted life years in China and globally from 1990 to 2021 - Ma, Chao; Chen, Linlin (Frontiers in Epidemiology, 2025)
BackgroundUrolithiasis significantly affects global health, contributing to substantial morbidity, healthcare costs, and reduced quality of life. Understanding temporal changes in the incidence, prevalence, mortality, and age-standardized disability-adjusted life year rates (ASDR) associated with urolithiasis is crucial for public health planning. However, few studies have systematically compared national and global trends, particularly in countries undergoing rapid healthcare transformation, such as China.MethodsUsing data from the Global Burden of Disease database from 1990 to 2021, we assessed the age-standardized incidence rate (ASIR), prevalence rate (ASPR), mortality rate (ASMR), and ASDR associated with urolithiasis in China and globally. Joinpoint regression was used to identify trend changes, and sex-specific subgroup analyses were performed.ResultsFrom 1990 to 2021, China showed substantial declines in all burden metrics: ASIR (−1.99%), ASPR (−1.99%), ASMR (−3.83%), and ASDR (−3.27%). Global declines were more modest: ASIR (−0.81%), ASPR (−0.81%), ASMR (−1.20%), and ASDR (−1.05%). Males consistently bore a higher burden.ConclusionsThe burden of urolithiasis has declined markedly from 1990 to 2021, with China showing greater improvements than the global average. This divergence suggests that systemic health reforms and expanded coverage may have contributed to the observed trends. Comparative findings imply that promoting equitable access to prevention and early intervention could be beneficial, particularly in resource-limited settings.